Pollination of the apple tree. II. Cultivars Starkrimson, Blackjon and Hawaii - Pasqual, Moacir; Petri, José; Pereira, Adilson José (Pesquisa Agropecuaria Brasileira, 2014)
The experiment was undertaken in 1978/1979 and 1979/1980, in São Joaquim (preferential region I) and Caçador (preferential region III), Santa Catarina, with pollinations on the following apple tree cultivars (Malus domestica, Borkh.): Starkrimson x (Gala, Fuji, Golden Delicious, Willie Sharp, Granny Smith, Mollie's Delicious, Delcon and Blackjon) - free pollination, self-fertility and parthenocarpy; 'Blackjon' x ('Starkrimson', 'Willie Sharp', 'Gala' and 'Delcon') - free pollination, self-fertility and parthenocarpy; and 'Hawaii' x ('Gala', 'Fuji' and 'Golden Delicious'). It was used a complete randomization, with four replications and 50 flowers/plot in each cultivar. It was also determined the percentage of pollen germination, the number of anthers and the number of grains of pollen in each anther. There was compatibility in minor or major degree among all cultivars tested, and the best combinations obtained were with 'Starkrirnson' x ('Gala. 'Fuji', 'Golden Delicious’ and Willie Sharp'); 'Blackjon' x ('Starkrimson', Willie Sharp' and 'Gala'); and 'Hawaii' x ('Gala' and 'Fuji'). The taxes of self-fertility and parthenocarpy were insufficient to permit a commercial production. The germination of pollen was good and the number of grains of pollen in each anther was low in these three cultivars.